P075 Efficacy and safety of switching to EVG/COBI/FTC/TAF in virologically suppressed women. (8th June 2017) - Hodder, Sally; Squires, Kathleen; Kityo, Cissy; Avihingsanon, Anchalee; Plotnikova, Yulia; Jiang, Shuping; Kulkarni, Rima; Cheng, Andrew; Elliott, Cindy; Cao, Huyen
Abstract : Introduction: Elvitegravir/cobicistat/emtricitabine/tenofovir disoproxil fumarate(E/C/F/TDF) demonstrated superior efficacy when compared with atazanavir boosted by ritonavir(ATV/r+F/TDF) in 575 treatment naïve women at Week(W) 48. We now report the safety and efficacy of subsequent switching to E/C/F/tenofovir alafenamide(TAF) versus remaining on ATV/r+F/TDF. Methods: After completing the initial randomised, blinded 48-week trial, women on ATV/r+F/TDF were randomised 3:1 to receive open label E/C/F/TAF versus remaining on their current regimen. Viral suppression by FDA snapshot analysis, pre-defined bone and renal safety and tolerability endpoints 48 weeks after switch are reported. Women who become pregnant while on study are given the option to continue study drug. Results: 212 HIV-infected, virologically suppressed women were randomised(E/C/F/TAF n=159, ATV/r+F/TDF n=53). Virologic suppression(<50c/mL) was maintained in 94.3% on E/C/F/TAF vs 86.8% on ATV/r+F/TDF with virologic failure in 1.9%, 3.8%, respectively. More women on E/C/F/TAF achieved <20c/mL at W48 compared with ATV/r+F/TDF (84.9% versus 71.7%p=0.041). No treatment emergent resistance was detected in either group. Mean% increase in BMD was higher in the TAF group for both lumbar spine and total hip. Multiple markers of renal safety were improved for participants randomised to TAF. No cases of proximal renal tubulopathy were reported. Nineteen women became pregnant during the switch study 13 E/C/F/TAF, 6 ATV/r+F/TDF, 3 normal infants have been delivered in each group to date. Discussion: These data demonstrate that women who switch to an integrase inhibitor+TAF-based regimen maintain high levels of virologic suppression with improvement in BMD and renal function biomarkers compared with those remaining on their ATV/r+TDF-based regimen.